Troubadour saint — Troubadour inconnu ? (Encore sur le Jubilus) - Majorossy, Imre Gábor (Verbum – Analecta Neolatina, 2005)
The following study continues the long-lasting debate on the authentic interpretation of the famous poem Dulcis Iesu memoria. As part of a major work, the paper shows the literary character of the deeply religious poem, still very popular these days, underlining its troubadour features. As the English origin of the poem has been revealed by André Wilmart, philological problems are not treated here; however, the mainstream tradition is accepted in a particular way: Saint Bernard did not write but did inspire the poem. It was the specific cultural and literary environment that exerted an obvious influence on the author, on the troubadour saint and inconnu as well.